Photo-Fenton self-cleaning carbon fibers membrane supported with Zr-MOF@Fe2O3 for effective phosphate removal from algae-rich water. (May 2023) - Zeng, Sen; Liu, Yuanshang; Wang, Yanmin; Wang, Yunhua; Zhou, Yaming; Li, Lihuang; Li, Shuo; Zhou, Xi; Wang, Miao; Zhao, Xueqin; Ren, Lei
Abstract: Adsorbents featuring abundant binding sites and high affinity to phosphate have been used to resolve water eutrophication. However, most of the developed adsorbents were focused on improving the adsorption ability of phosphate but ignored the effect of biofouling on the adsorption process especially used in the eutrophic water body. Herein, a novel MOF-supported carbon fibers (CFs) membrane with high regeneration and antifouling capability, was prepared by in-situ synthesis of well-dispersed MOF on CFs membrane, to remove phosphate from algae-rich water. The hybrid UiO-66-(OH)2 @Fe2 O3 @CFs membrane exhibits a maximum adsorption capacity of 333.3 mg g −1 (pH 7.0) and excellent selectivity for phosphate sorption over coexisting ions. Moreover, the Fe2 O3 nanoparticles anchored on the surface of UiO-66-(OH)2 through 'phenol-Fe(III)' reaction can endow the membrane with the robust photo-Fenton catalytic activity, which improves long-term reusability even under algae-rich condition. After 4 times photo-Fenton regenerations, the regeneration efficiency of the membrane could remain 92.2%, higher than that of hydraulic cleaning (52.6%). Moreover, the growth of C. pyrenoidosa was significantly reduced by 45.8% within 20 days via metabolism inhibition due to membrane-induced P-deficient conditions. Hence, the developed UiO-66-(OH)2 @Fe2 O3 @CFs membrane holds significant prospects for large-scale application in phosphate sequestration of eutrophic water bodies. Graphical abstract: Image 1 Highlights: A robust Zr-MOF@Fe2 O3 -based membrane was prepared by in situ growth combined with 'phenol-Fe(III)' reaction. The membrane exhibited a high adsorption capacity for phosphate. The membrane with photo-Fenton self-cleaning ability showed excellent biological antifouling capability. The membrane possessed long-term reusability even under algae-rich conditions.